A comparison of activated carbon remediation success in floodplain soils contaminated with DDT and its metabolites using ex situ and in situ experimentation. (15th February 2022) - Harwood, Amanda D.; Nutile, Samuel A.; Simpson, Adam M.
Abstract: Remediation of hydrophobic organic contaminants using activated carbon is an effective means by which to clean up contaminated areas. Predicting remediation success using laboratory experimentation with soil, however, is unclear. Current remediation efforts involving activated carbon addition to floodplain soils downstream of the Velsicol Chemical Corporation Superfund Site (VCCSS) have offered the opportunity to directly compare in situ activated carbon remediation with laboratory experimentation. The objective of the current study was to compare bioaccumulation of DDT, DDD, and DDE (DDX) residues by earthworms ( Eisenia fetida ) exposed to laboratory-aged (LA) or field-aged (FA) soils from four locations. Samples were evaluated at 0-, 3-, and 9-months post-remediation to determine the ability of laboratory studies to predict in situ remediation. Floodplain soils downstream from the VCCSS were amended with 2% by weight activated carbon in the field and the laboratory, and then aged for 3- or 9-months. At 0-, 3-, and 9-months bioaccumulation assays were conducted with LA and FA soils and tissue concentrations were compared within study sites. In both LA and FA soils, activated carbon caused significant reductions (37.01–92.94%) in bioaccumulated DDX in earthworms. Field-collected worms showed a similar trend in reduction of bioaccumulated DDX, suggesting activated carbon remediation was successful in reducing bioavailable DDX for native organisms within the floodplain soils. The rate of reduction in bioavailable DDX, however, was significantly faster in LA soils (β = −0.189, p < 0.0001) compared to FA soils (β = −0.054, p < 0.0038). Differences in temperature and methods of activated carbon incorporation between LA and FA soils may account for the differences in remediation rate, suggesting laboratory experiments may overpredict the extent or speed in which remediation occurs in the field. Therefore, use of laboratory studies in predicting success of activated carbon remediation may be most effective when conditions mimic field remediation as closely as possible. Graphical abstract: Image 1 Highlights: Activated carbon effectively remediates organic contamination in sediments. Evidence in soil and applicability of lab experiments to the field is lacking. Activated carbon reduced earthworm DDX bioaccumulation in lab and field. Lab-aged soils showed faster declines in bioavailability than field soils. Lab experiments should mimic field application to predict remediation.